Urban Sufisme di Era Digital dan Urban Salafi di Era Kontemporer - Ridwan Ridwan; Hamzah Harun; Muhaimin Muhaimin (Pusat Penelitian dan Pengabdian Masyarakat (P3M) Sekolah Tinggi Ilmu Islam dan Bahasa Arab (STIBA) Makassar, 2024)
This study aims to investigate the adaptation of Sufi and Salafi thought in response to social, cultural, and technological changes in the contemporary era marked by rapid urbanization and digitalization. The research employs a qualitative approach with a focus on text analysis to depict how these two streams adapt to the dynamics of digitized urban environments. Data collection involves participatory observation and document analysis. The findings indicate that Sufism and Salafism are significant phenomena in contemporary Islam undergoing substantial adaptation to modern urban social, cultural, and technological changes. Sufism encounters new challenges and opportunities in the digital age, utilizing technology to disseminate its teachings globally. Meanwhile, Salafism emphasizes a return to pure Islamic teachings and faces challenges such as negative stigma and interactions with evolving societal norms. Both streams not only reflect the complexity of modern Islamic societies but also play crucial roles in shaping the religious identities and practices of individuals amidst the evolving social and technological dynamics. The implications of this research can support the development of strategies or policies promoting social harmony and religious integration in complex and evolving urban environments.